2015
DOI: 10.5732/cjc.014.10252
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation in female cancer patients: a single center experience

Abstract: Advances in cancer treatment allow women to be cured and live longer. However, the necessary chemotherapy and radiotherapy regimens have a negative impact on future fertility. Oncofertility has emerged as a new interdisciplinary field to address the issue of gonadotoxicity associated with cancer treatment and to facilitate fertility preservation, including oocyte and ovarian tissue cryopreservation. These fertility issues are often inadequately addressed, and referral rates to oncofertility centers are low. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 26 publications
1
31
0
1
Order By: Relevance
“…1) 3, 4 . Although glucose and fructose catabolism in a normal liver have been well studied, it is unknown whether these sugars are distinctly metabolized to promote development of hepatocellular carcinoma (HCC), one of the most aggressive cancers with a median survival time shorter than 1 year 57 .…”
mentioning
confidence: 99%
“…1) 3, 4 . Although glucose and fructose catabolism in a normal liver have been well studied, it is unknown whether these sugars are distinctly metabolized to promote development of hepatocellular carcinoma (HCC), one of the most aggressive cancers with a median survival time shorter than 1 year 57 .…”
mentioning
confidence: 99%
“…Access to resources for these patients is reduced and protocols to establish tele‐health services and other support services to these patients is ongoing . Reassuringly, some studies have demonstrated that distance from fertility services did not significantly impact on patient choice of uptake of fertility preservation . Following a recent study by Ussher et al ., simple resources including fact sheets, information booklets, decision aids and consultation checklists may aid in improving care provided to patients not living in metropolitan areas …”
Section: Resultsmentioning
confidence: 99%
“…46 Reassuringly, some studies have demonstrated that distance from fertility services did not significantly impact on patient choice of uptake of fertility preservation. 56 Following a recent study by Ussher et al, simple resources including fact sheets, information booklets, decision aids and consultation checklists may aid in improving care provided to patients not living in metropolitan areas. 54 With any fertility treatment, both ethical and financial considerations need to be addressed with patients.…”
Section: Service Delivery Framework For Adolescents and Young Adultsmentioning
confidence: 99%
“…La preservación de la fertilidad ante casos de tumores malignos en mujeres que van a recibir tratamientos altamente gonadotóxicos está bien protocolizada (12) (13). La reserva ovárica se ve afectada tras la extirpación de quistes ováricos (14) (15).…”
Section: Discussionunclassified